2017
DOI: 10.1103/physreve.96.022154
|View full text |Cite
|
Sign up to set email alerts
|

Jammed systems of oriented needles always percolate on square lattices

Abstract: Random sequential adsorption (RSA) is a standard method of modeling adsorption of large molecules at the liquid-solid interface. Several studies have recently conjectured that in the RSA of rectangular needles, or k-mers, on a square lattice, percolation is impossible if the needles are sufficiently long (k of order of several thousand). We refute these claims and present rigorous proof that in any jammed configuration of nonoverlapping, fixed-length, horizontal, or vertical needles on a square lattice, all cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 34 publications
(43 reference statements)
11
43
0
Order By: Relevance
“…We have presented a parallel algorithm which is very efficient in terms of speed and memory usage. Our results are in agreement with the previously obtained results of [11,12,16] and we have obtained the percolation and jamming concentrations for lengths of k-mer up to 2 17 . The ratios of percolation and jamming densities show quite different behavior for k 500 compared to the behavior for k ≤ 512.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have presented a parallel algorithm which is very efficient in terms of speed and memory usage. Our results are in agreement with the previously obtained results of [11,12,16] and we have obtained the percolation and jamming concentrations for lengths of k-mer up to 2 17 . The ratios of percolation and jamming densities show quite different behavior for k 500 compared to the behavior for k ≤ 512.…”
Section: Discussionsupporting
confidence: 93%
“…(7) is in agreement with the results of [16]. We have generalized the results of [16] for the case of periodic boundary conditions in Appendix A and have proved that, in thermodynamic limit, percolation always occurs before jamming. 14 and L = 1 638 400 for k > 2 14 .…”
Section: A Percolating Threshold Jamming Coverage and Their Ratiossupporting
confidence: 86%
“…This finding reinforces the theoretical analysis in Ref. [15], namely, in the case of linear k-mers on square lattices, percolation always occurs before jamming.…”
Section: Introductionsupporting
confidence: 91%
“…In a very recent paper, Slutskii et al [16], using simulation techniques, corroborated the result reported by Kondrat et al [15]. Based in a very efficient parallel algorithm, the authors studied the problem of large linear k-mers (up to k = 2 17 ) on a square lattice with periodic boundary conditions.…”
Section: Introductionsupporting
confidence: 54%
“…Tarasevich et al [32,33] conjectured, based on simulation, that for k-mers of sufficient length (k 1.2 × 10 4 ) percolation does not occur. More recently, Kondrat et al [34] developed a rigorous proof refuting this conjecture. They showed that for nonoverlapping k-mers, the jammed configuration includes a percolating cluster.…”
Section: Introductionmentioning
confidence: 93%